Formação continuada de professores em geometria por meio de uma plataforma de educação a distância: uma experiência com professores de ensino médio - Santos, Jefferson Almeida (2007)
This research is due to introduce a persuade proposal in Geometry to Math teachers, in which they can be in contact with researches results about Geometry learning, to think about their classroom practical and change experiences with other teachers, by using, to that, a distance educational platform called Moodle. To this, we have gotten and we have implemented a course Geometry Topics , that had five virtual meetings and two attendance meetings where we have talked about Geometry contents, by reading texts fragments of authors like Marc Rogalski, Aline Robert, Raymond Duval, Régine Douady and Bernard Parsysz. The quantitative analysis was taken from the interactions and created and developed activities during the meetings in the Moodle forum ambient, and they had pointed to a new teachers attitude about the activities that have to be developed with their students, after this. We have concluded that the Internet and computers teachers´ access, the partnership between researchers and educational institutions, to mix the distance meetings with attendance moments to reflect about, and the choose of working with researches subjects and not with specifical contents were elementaru facts in this research development